Experimental Investigation on Web Crippling Property of High-Strength Cold-Formed (HSCF) Rectangular Steel Tube - Xianglong Liu; Jicheng Zhang; Yuanqi Li; Lei Zeng; Guofeng Du (Advances in Civil Engineering)
To research the web crippling performance (i.e., the ultimate web crippling bearing capacity and ductility) of high-strength cold-formed (HSCF) rectangular steel tubes under concentrated load, thirty-six specimens with different bearing plate width, width-to-height ratio, boundaries, and loading conditions are fabricated and tested in this paper. Particularly, four kinds of boundaries and loading conditions are utilized, including end-two-flange (ETF), end-one-flange (EOF), interior-two-flange (ITF), and interior-one-flange (IOF). Research revealed the failure modes of HSCF rectangular steel tubes under concentrated loads applied at the end or interior. Moreover, the load-displacement curves and load-strain curves are obtained. The results show that the ultimate crippling capacity of webs increases significantly with larger bearing plate width and width-to-height ratio. Specimens subjected to interior bearing load have higher ultimate strength and deformation capacity than counterparts that are subjected to bearing load at the end. Additionally, in the middle of the compression web, all strain measuring points enter the plasticity stage and finally appear in the plastic hinge area. Subsequently, the failure modes and ultimate bearing capacity are simulated by the finite element method (FEM), which is implemented via ABAQUS. By comparing the test results with the numerical values, demonstrate the effectiveness of the proposed numerical simulation on investigating the failure modes and the ultimate bearing capacity of HSCF rectangular steel tubes. Finally, regarding the conservative and dangerous calculation of web crippling ultimate bearing capacity in current codes, we can provide a good guidance for future work, particularly the proposed calculation equations for ultimate bearing capacity of HSCF rectangular steel tubes.